High-efficiency, single-stage 7-kHz high-average-power ultrafast laser system - Murnane, Margaret M., author; Kapteyn, Henry C., author; Dollinger, Robert, author; Thompson, Sarah, author; Bartels, Randy, author; Backus, Sterling, author; Optical Society of America, publisher (Colorado State University. Libraries, 2001)
We demonstrate a simple and practical single-stage ultrafast laser amplifier system that operates at a repetition frequency from 1 to 10 kHz, with millijoule pulse energy and as much as 13 W of average power. The repetition rate can be adjusted continuously from 1 to 10 kHz by new all-solid-state pump laser technology. This is to our knowledge the highest average power ever obtained from a single-stage ultrafast laser amplifier system. This laser will significantly increase the average power and the repetition rate that is easily accessible for high-field experiments such as coherent x-ray generation or for laser-synchrotron studies.